Azetidine‐Containing Alkaloids Produced by a Quorum‐Sensing Regulated Nonribosomal Peptide Synthetase Pathway in Pseudomonas aeruginosa. (14th January 2019) - Hong, Zhilai; Bolard, Arnaud; Giraud, Caroline; Prévost, Sébastien; Genta‐Jouve, Grégory; Deregnaucourt, Christiane; Häussler, Susanne; Jeannot, Katy; Li, Yanyan
Abstract: Pseudomonas aeruginosa displays an impressive metabolic versatility, which ensures its survival in diverse environments. Reported herein is the identification of rare azetidine‐containing alkaloids from P. aeruginosa PAO1, termed azetidomonamides, which are derived from a conserved, quorum‐sensing regulated nonribosomal peptide synthetase (NRPS) pathway. Biosynthesis of the azetidine motif has been elucidated by gene inactivation, feeding experiments, and biochemical characterization in vitro, which involves a new S ‐adenosylmethionine‐dependent enzyme to produce azetidine 2‐carboxylic acid as an unusual building block of NRPS. The mutants of P. aeruginosa unable to produce azetidomonamides had an advantage in growth at high cell density in vitro and displayed rapid virulence in Galleria mellonella model, inferring functional roles of azetidomonamides in the host adaptation. This work opens the avenue to study the biological functions of azetidomonamides and related compounds in pathogenic and environmental bacteria.